Peran Ijarah dalam Meningkatkan Akses Pembiayaan Mikro Syariah - Lika Handayani; Miti Yarmunida; Nenan Julir (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Sharia Micro Enterprises are one of the main pillars of the national economy. Micro businesses must receive protection as a form of government support for the community. However, there are several obstacles for people in developing their businesses, one of which is capital. The aim of this research is to facilitate access for micro business actors to finance with ijarah contracts. namely an alternative solution to a source of financing for Micro Businesses that is easily accessible, especially for the Indonesian people who are predominantly Muslim, namely financing with an ijarah agreement. The problem discussed in this research is what is the role of the ijarah contract in increasing access to sharia micro financing. It can be seen that the ijarah contract plays a very important role in supporting business development for micro business actors and providing easy access to financing services so that it can help the development of business actors. The method used in this research is a qualitative descriptive research method. The data sources used in this research are secondary and primary data. The data collection technique used in this research is literature study. . The results of this research are that the ijarah contract plays a very important role in the development of sharia micro businesses. The Al-Qur'an and Hadith also emphasize that the good practice of the ijarah contract is very easy and provides easy access for business actors to carry out financing for the development of a business, besides that it also aims to support implementation of national development in order to increase the distribution of social welfare. Therefore, for the Indonesian people who are predominantly Muslim, the ijarah contract is an alternative source of financing and easy access in developing their business in accordance with Islamic law.